The color revolution - Blaszczyk, Regina Lee (MIT Press ; in association with Lemelson Center, Smithsonian Institution, 2012)
A history of color and commerce from haute couture to automobile showrooms to interior design.- Resumé vydavatel
Keywords: design -- dějiny; barvy -- dějiny; marketing; spotřebitelské chování -- dějiny; design -- history; colors -- history; consumer behavior -- history; produktový design; elektronické knihy; monografie; electronic books; monographs